Uma leitura da Gaudium et Spes na perspectiva de mulheres latino-americanas - Domezi, Maria Cecília (Revista Eclesiástica Brasileira, 2006)
À luz da mensagem da mulher siro-fenícia (Mc 7,24-30 e Mt 15,21-28), aqui se busca, com uma consciência crítica de gênero, uma compreensão do documento Gaudium et Spes, por sua linha humanista e aberta ao processo da modernidade. Embora, no Concílio Vaticano II, o patriarcalismo tenha persistido nas práticas, houve esforços para sua superação e, principalmente, possibilidades simbólicas importantes na perspectiva da igualdade de gênero e na valorização da sexualidade humana. Abstract: In the light of the Syrian-Phoenician woman’s message (Mk:7:24-30 and Mt.15:21-28) and with a critical awareness of gender, we seek a greater understanding of the document Gaudium et Spes because of its humanistic and direct approach to the process of modernity. Although in the Vatican II Council patriarchalism may have persisted in the Catholic practices, there have been efforts to overcome it and, in particular, important symbolical possibilities emerged in the perspective of gender equality and in the valorization of human sexuality.